Ámbitos de justificación biográfica de la decisión de no tener hijos (2021)
From biographical routes of adults who have decided not to have children and not to exercise maternity or paternity roles, justification devices in the context of overpopulation and environmental responsibility are analyzed. A qualitative, phenomenological study was conducted with in-depth interviews with adults, residents in different cities of Colombia, who decided not to be mothers or not to be fathers. It is concluded that the decision not to have children is a kind of biographical fracture that violates the social precepts on reproduction and how the issue of overpopulation and environmental crisis is the best social context of legitimizing decisions not to have children.